Fluorescent aminoquinolines responsive to micelles’ surface charge - Pastrello, Bruna [UNESP]; da Silva-Filho, Luiz Carlos [UNESP]; Ximenes, Valdecir Farias [UNESP] (Elsevier, 2025)
Micelles are clusters of surfactant molecules used in various scientific and technological applications. One crucial characteristic of micelles is their surface electric charge. This study describes the development of fluorescent aminoquinolines (AQs) that are sensitive to the surface charge of micelles. The AQs were synthesized using a one-pot synthetic procedure. When incorporated into micelles, the AQs showed a significant increase in fluorescence at 480 nm, which helped in determining the critical micelle concentration of anionic (sodium dodecyl sulfate, SDS), cationic (hexadecyltrimethylammonium bromide, CTAB), and neutral (Triton-X100) surfactants. More importantly, only negatively charged micelles produced an exclusively red-shifted fluorescence band centered at 596 nm. The interaction with SDS shifted the equilibrium towards the protonated form of AQ, leading to the red-shifted band. AQ incorporated in SDS was more sensitive to the electron donor quencher N,N-dimethylaniline (Ksv = 8.6 × 103 M−1) than the electron acceptor naphthalene-2-carbonitrile (Ksv = 0.58 × 103 M−1), revealing its unique electronic feature in negative micelles. The opposite effect was observed in CTAB and Triton X-100. By analyzing the fluorescence quenching caused by N,N-dimethylaniline, the aggregation number of SDS micelle was determined (Nagg = 61), which matched the existing literature. These experimental findings underscore the use of AQ as a fluorescent probe for differentiating the surface charge of micelles.
Keywords: Aggregation number; Aminoquinolines; Critical micelle concentration; Fluorescent probe; Micelle surface charge